Penerapan Kecerdasan Buatan Untuk Deteksi Trafik Jaringan Tidak Wajar Berbasis Phyton Jurusan Teknik Jaringan Komputer - Jusuf Wahyudi; Ahmad Asyhari; Rizka Tri Alinse; Wahyu Hidayat; Kharien Eka Putri (Jurnal Dehasen Untuk Negeri, 2024)
This community service activity is motivated by the gap in students’ understanding of information technology developments, particularly in network security and artificial intelligence. The purpose of this activity is to provide education on the application of artificial intelligence to detect abnormal network traffic and to enhance students’ readiness in facing technological advancements. The method used is interactive socialization and education through presentations, discussions, and question-and-answer sessions. The activity was conducted through preparation, implementation, and evaluation stages. The results indicate an improvement in students’ knowledge and understanding of network technology and artificial intelligence. In addition, participants showed high enthusiasm during the activity, as reflected in active participation and numerous questions raised. This activity also had a positive impact on increasing students’ motivation to learn more about information technology. Therefore, this program contributes to reducing the digital gap and improving students’ competencies to better prepare them for challenges in the technological era.